P197 Incidence and management of immunotherapy-induced colitis in a tertiary melanoma and IBD centre: Clinical practice data. (16th January 2018) - Cheung, V; Gupta, T; Payne, M; Middleton, M; Brain, O
Abstract: Background: Checkpoint inhibitors are a novel anti-cancer therapy that are standard of care in metastatic melanoma, non-small cell lung and renal cancer. 1 CTLA-4 inhibitors (e.g. Ipilimumab) and PD-1 inhibitors (Nivolumab, Pembrolizumab) can be used separately or in combination for melanoma. Their immune inhibition is non-specific, leading to a number of immune-related adverse events (irAEs) including colitis, hepatitis and pancreatitis. 2 Combination therapy is known to cause more irAEs than single-agent CTLA-4 inhibition. There are limited real-world clinical data describing the incidence and management of these GI irAEs. The aims this study were (1) To determine the incidence of GI irAEs in a tertiary oncology centre and (2) to analyse the management and outcome of GI irAEs within a tertiary oncology and IBD centre. Methods: Retrospective single–centre review. Melanoma patients receiving Ipilimumab ± Nivolumab between Dec 2011 and June 2017 were identified from the oncology prescribing database. The electronic patient record (EPR) was used to determine the incidence of GI side effects. Investigations, treatment, and outcome data were collated. Results: 153 patients who received immunotherapy were identified. There was a higher incidence of diarrhoea and hepatitis ( n = 21/28, 75%) in those receiving dual therapy vs. monotherapy ( n = 25/115, 22%). The incidence of diarrhoea for dual therapy ( n = 18/28, 64%) was in excess of that described in trial data (44%) [3] . Diarrhoea incidence for CTLA-4 inhibition was similar to published data (20% vs. 33% 3 ). Dual therapy resulted in more frequent use of infliximab (22%) vs. monotherapy (15%). Colitis was generally associated with a raised CRP and low albumin. There was significant variability in symptoms, time of onset, and in management decisions. Conclusions: Dual therapy with CTLA-4 and PD-1 inhibitors may result in a higher incidence of colitis than described in clinical trials. Although guidelines exist [2], there is no clear biological threshold for timing of therapy initiation and escalation, resulting in variability in care. This case series demonstrates that irAE colitis is a common problem that has implications for healthcare provision and care standardisation. Complete management and outcome data will be presented. References: 1. Gupta A, et al . Systematic review: colitis associated with anti-CTLA-4 therapy. Aliment Pharmacol Ther 2015;42:406–417. 2. Cheng R, et al . Ipilimumab-induced toxicities and the gastroenterologist. J Gastroenterol Hepatol 2015;30:657–666. 3. Larkin J, et al . Combined nivolumab and ipilimumab or monotherapy in untreated melanoma. N Eng J Med 2015;373:23–34.